Compliance of tuberculosis patients with treatment in Bangkok chest clinic Thailand. - Kandel, Shyam Lal (2000)
ABSTRACT: This cross -sectional study aimed to determine the compliance of tuberculosis patients with treatment in the Bangkok Chest Clinic, in Thailand. One hundred eighty respondents who completed one-month treatment and came for drug collection from 6th to 28th march 2000 at the Bangkok chest clinic were interviewed by structured questionnaire. The result of this study revealed that 78.3 percent of the patients had compliance behavior with their treatment. More than two thirds, 83.3 percent were in an economically productive age group. Most of them were male (70.0%) had lower primary level of education, and were daily wage labors, street venders of had no employment. About 63.3percent had monthly family income of less than 5,000 Baht. Results showed a significant association between family knowledge about impact of irregular or default treatment and compliance of patients with treatment (p-value 0.035). In addition a significant negative association between given information about separate utensil and compliance of patient with treatment was supported by a p-value 0.041. The respondents in higher age groups, single marital status, primary level of education, small family size and low-income group had higher compliance as compared to younger age groups, married, secondary and higher secondary level of education, large family size, and higher income groups. It sis suggested from the study that policy makers and service providers should consider the assessment of the contents of health education messages, methods of communication, in order to decrease the gap between health service provider and patients. patients should keep daily records in the patients Treatment Identity Card to better remember their taking of medications.